Anisotropy in the magnetic interaction and lattice-orbital coupling of single crystal Ni3TeO6 - Anirudha Ghosh (Nature Portfolio, 2018)
Abstract This investigation reports on anisotropy in the magnetic interaction, lattice-orbital coupling and degree of phonon softening in single crystal Ni3TeO6 (NTO) using temperature- and polarization-dependent X-ray absorption spectroscopic techniques. The magnetic field-cooled and zero-field-cooled measurements and temperature-dependent Ni L 3,2-edge X-ray magnetic circular dichroism spectra of NTO reveal a weak Ni-Ni ferromagnetic interaction close to ~60 K (T SO: temperature of the onset of spin ordering) with a net alignment of Ni spins (the uncompensated components of the Ni moments) along the crystallographic c-axis, which is absent from the ab-plane. Below the Néel temperature, T N~ 52 K, NTO is stable in the antiferromagnetic state with its spin axis parallel to the c-axis. The Ni L 3,2-edge X-ray linear dichroism results indicate that above T SO, the Ni 3d e g electrons preferentially occupy the out-of-plane 3d 3z 2 −r 2 orbitals and switch to the in-plane 3d x 2 −y 2 orbitals below T SO. The inherent distortion of the NiO6 octahedra and anisotropic nearest-neighbor Ni-O bond lengths between the c-axis and the ab-plane of NTO, followed by anomalous Debye-Waller factors and orbital-lattice in conjunction with spin-phonon couplings, stabilize the occupied out-of-plane (3d 3z 2 −r 2) and in-plane (3d x 2 −y 2) Ni e g orbitals above and below T SO, respectively.